Microemulsions: Unique Properties, Pharmacological Applications, and Targeted Drug Delivery - Suhail, Nida; Alzahrani, A. Khuzaim; Basha, W. Jamith; Kizilbash, Nadeem; Zaidi, Arsalan; Ambreen, Jaweria; Khachfe, Hassan M. (Frontiers in Nanotechnology, 2021)
Microemulsions comprising of oil, water and a surfactant, in association with some co-surfactants are highly thermodynamically stable systems. They have found applications in a large number of chemical and pharmacological processes due to their unique properties such as large interfacial area, low interfacial tension, and most importantly, the ability to solubilize and deliver hydrophobic drugs. In addition to the oral and intravenous route, they are suitable for continual and targeted delivery through the ophthalmic, vaginal, pulmonary, dental, and topical routes. This review highlights the properties and several recent developments in the use of microemulsions for medical treatment purposes including targeted drug delivery.